Experimental Analysis and Application of All-Metal Conical Progressive Cavity Pump - Chen Xiaochun (Shiyou jixie, 2025)
The stator and rotor of all-metal progressive cavity pump adopt a clearance fit， and fluids of different viscosities require different clearances to achieve optimal production status. In this paper， a new type of all-metal conical progressive cavity pump oil production system was developed. The stator and rotor of the progressive cavity pump adopts a conical structure， achieving a two-way adjustment of the stator and rotor clearance through a surface rotational lifting assembly. The above-ground protection assembly can compensate the tubing length variation and prevent the tubing from tripping. The balancing assembly can keep the stator and rotor clearance stable in the production process. Then， a 20 m test well was constructed to analyze the influence of rotor position on the operating characteristics of the pump， showing that when the rotor position is reduced to 6 mm， the volumetric efficiencies corresponding to 5 MPa and 10 MPa working pressure differences are 98.2% and 75.4% respectively， while the pump efficiency reaches its highest level， which is 49.6% and 38.9% respectively. As the rotor position further decreases， the volumetric efficiency increases slowly， the friction between the stator and rotor intensifies， and the mechanical efficiency sharply decreases. When the rotor position is greater than 10 mm， as the rotor position increases， the mechanical efficiency corresponding to a working pressure difference of 5 MPa is about 50%–55%， and there is a downward trend. Considering all factors， the rotor position should be greater than 10 mm during operation. Finally， the all-metal conical progressive cavity pump was applied in thermal recovery heavy oil well of Xinchun oilfield. The field application results show that compared to oil production with pumping unit in offset well， the all-metal conical progressive cavity pump increases production time by 52.1% and liquid production by 15.2%， reduces daily average power consumption by 64.3% and power consumption per ton of liquid by 52.7%. Compared to oil production with pumping unit in the same well， the daily average liquid production is increased by 39.4%， the daily average power consumption is decreased by 66.6%， and the power consumption per ton of liquid is decreased by 76.1%. The research results show that the oil production system meets the requirements of efficient lifting of oilfields， and especially has good adaptability to thermal recovery heavy oil wells.